The Effect of Principal’s Managerial Competence and Teacher’s Professional Competence on the Educational Quality of Public Senior High Schools - Karmila, Karmila; Lian, Bukman; Wardiah, Dessy (Yayasan Sembilan Pemuda Indonesia, 2023)
One of the abilities required of a school administrator as a leader is managerial competency. Principals may effectively manage education if they have excellent managerial skills, just as teachers must have professional skills in order to carry out their tasks. Management and professional skills are both essential for school principals and instructors. It is envisaged that these abilities would improve educational quality. As a result, this study was done to investigate the impact of school administrators’ administrative competency and teachers’ professional competence on educational quality. This research will be carried out utilizing a quantitative descriptive technique. According to the findings of this study, when examined independently, the administrative competency of school principals has a significant impact on the quality of education. Teacher professional competence has a positive and considerable effect on educational quality and is in the moderate range. According to the simultaneous test, the principal’s administrative competence and the teacher’s professional competence had a positive and substantial impact on the quality of education at SMA Negeri in Kayuagung, with a reasonably high degree of influence.